Effect of Processing Parameters on Wear Properties of Hybrid AA1050/Al2O3/TiO2 Composites - Yuanfei Gao; Mohammad Heydari Vini; Saeed Daneshmand; Ameer A. Alameri; Omrane Benjeddou; Raed H. C. Alfilh (Crystals, 2023)
In this study, hybrid AA1050/Al2O3/TiO2 composites have been produced via combined liquid casting and powder metallurgy techniques. Degassing was utilized to improve the wettability of molten aluminum alloys, and then successful bonding was generated between aluminum matrix and reinforcement particles during the powder metallurgy technique. As the base matrix and reinforcements, AA1050 alloy, Al2O3 and TiO2 particles were taken, respectively. Then, content values of 5Wt.% of Al2O3 in the mesh size of 20 μm and 2.5 and 5 wt. % of TiO2 particles with mesh size of 5μm were added to the AA1050 matrix. For each composite sample, ceramic particles were warmed to 600°C in order to improve wettability and distribution. An identical scattering of subdivisions was observed through aluminum (as matrix) in the microstructural study. To measure the wear resistance, the mechanism of rotary wear test was used. The achieved results illustrated that the fabrication of hybrid composites is an ideal approach to improve the wear resistance of Al-based composites. By increasing of TiO2 Wt.% up to 5% for all composite samples, the wear rate improved to less than half of the monolithic Al alloy value for each composite sample.